Labor and the State in Egypt - Tidjani, Bassirou (Relations industrielles / Industrial Relations, 2000)
The article reviews the book, "Labor and the State in Egypt," by Marsha Pripstein Posusney,
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z